Improving the Collaboration Skills of Vocational School Students Through Flipbook with Augmented Reality in Society 5.0 - Ghinaya, Zahra; Rahayu, Sri; Supriatna, Nandan (CIVED, 2024)
In the age of Society 5.0, digitalization has completely changed the educational landscape and made it necessary for schools to foster students' critical thinking, cooperation, communication, and creative thinking abilities. (4C). Students can be better prepared for change by attending vocational institutions, such as the Vocational School (SMK). The continued development of learning technologies is crucial, particularly those that rely on virtual learning. R&D (Research and Development) combined with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model is the research methodology used for the creation and assessment of learning media. Quasi-experimental (Non-equivalent Group Pretest Posttest Design) methods are used to measure students' increased capacity for collaboration through group controls and experiments. Two material experts and two media experts who are also students in class X at one of the Bandung SMKs serve as the subjects of the ADDIE model. Students in classes X.3 and X.4 are used for quasi-experimental procedures. The study's findings demonstrated that Flipbooks with augmented reality fell into a respectable category, with revisions observed in the presentations of 80.5% of subject matter experts and 80.8% of media professionals. In the experimental class, students' levels of collaboration were 91% with great categories, compared to 70% in the control class with good categories. These findings demonstrate how successfully using flipbooks with augmented reality can enhance SMK students' collaboration skills.